Usefulness of TNFR1 As Biomarker of Intracranial Aneurysm in Patients with Spontaneous Subarachnoid Hemorrhage - Torres, R (2020)
Aim: To determine the utility of TNF-α receptor (TNFR1) as a biomarker for the presence of aneurysms in patients with acute subarachnoid hemorrhage (SAH). Patient & methods: This is a prospective study in patients with acute spontaneous SAH. Arterial blood from catheter near aneurysm and peripheral venous blood samples are collected. TNFR1 levels were analyzed in patients with and without aneurysm. Results: 80 patients were included, 58 were analyzed. 41 patients (70.7%) had an aneurysm. Venous TNFR1 levels >1658 pg/ml had 46.3% sensitivity and 94.1% specificity for aneurysms presence. TNFR1 >1658 pg/ml was also an independent predictor for its presence (odds ratio = 12.03 [1.13-128.16]; p = 0.039). Conclusion: High levels of TNFR1 in peripheral venous blood are associated with the presence of aneurysm in patients with acute SAH.